2019
DOI: 10.29407/nor.v6i1.13080
|View full text |Cite
|
Sign up to set email alerts
|

Konstruksi Teknik Konseling Berbasis Budaya Model KIPAS untuk Meningkatkan Kecakapan Sosial dan Kematangan Karier Siswa

Abstract: Setiap budaya memiliki sistem nilai yang dapat menjadi strategi dan penguatan bagi siswa dalam menyelesaikan tugas perkembangan khususnya bidang sosial dan karier. Problematik yang menjadi sorotan pada generasi milenal saat ini ialah siswa kurang memiliki kecakapan hidup sosial yang produktif dan belum optimalnya kematangan karier untuk masa akan datang. Pendekatan konseling berbasis budaya model KIPAS dapat menjadi alternatif solusi untuk mengatasi problematik tersebut, karena sesuai dengan konteks budaya Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The research methods used are mostly qualitative studies. In terms of research findings, most researchers reported that the use of proverbs in the counseling process made a positive contribution to client change (Ariantini et al, 2019;Ciuffardi et al, 2013;Disassa & Into, 2020;Liu et al, 2012;McRobie & Agee, 2017;Owu-Ewie, 2019;Rahill et al, 2011;Zubaidah, 2019).Second, we find that proverbs and metaphors are two things that cannot be separated in the social reality of society because they are both cultural products. A proverbs in a psychosocial framework reflect the normative aspects of how people think and behave in social situations.…”
Section: Discussionmentioning
confidence: 57%
“…The research methods used are mostly qualitative studies. In terms of research findings, most researchers reported that the use of proverbs in the counseling process made a positive contribution to client change (Ariantini et al, 2019;Ciuffardi et al, 2013;Disassa & Into, 2020;Liu et al, 2012;McRobie & Agee, 2017;Owu-Ewie, 2019;Rahill et al, 2011;Zubaidah, 2019).Second, we find that proverbs and metaphors are two things that cannot be separated in the social reality of society because they are both cultural products. A proverbs in a psychosocial framework reflect the normative aspects of how people think and behave in social situations.…”
Section: Discussionmentioning
confidence: 57%
“…One of the school counselors' efforts to integrate guidance and counseling services with local wisdom is to use culturally charged counseling, namely the KIPAS model counseling. The KIPAS model of counseling has begun to be developed in various parts of Indonesia (Ariantini, Naser, & Hanafi, 2019;Fitri, Mappiare-AT, & Triyono, 2020;Habsy & Wahyuni, 2019;Hariko & Ifdil, 2017;Mappiare-AT, 2019;Sudirman, Kurniawan, Putri, Aiman, & Saputra, 2022). The development of KIPAS counseling in various regions of Indonesia is motivated by the cultural potential of regions in Indonesia so that it can be used as an alternative approach in providing services to students to help optimize aspects of student development in the competency standards for student independence.…”
Section: Discussionmentioning
confidence: 99%
“…They are suitable for counselors and counselees as an excellent option for schools in Indonesian cultural communities (Wahyuni & Gudnanto). This model became an option in the school primarily because it has a cultural content and several folk games favourable to teachers and students (Ariantini, Naser, & Hanafi, 2019;Ariantini & Suriata, 2019;Mappiare-AT & Fauzan, 2019). The cultural content is applied more as the etic than the emic position, and it is specific compared to universal approaches (Daya, 2001).…”
Section: Introductionmentioning
confidence: 99%